Dynamics of human capital development in economic development cycles - Yulia Gruzina; Irina Firsova; Wadim Strielkowski (Economies, 2021)
Our paper focuses on the dynamics of development of human capital in economic development cycles (as described, for example, in the works of Becker or Barro). In the course of this research, we created an econometric model based on the modified Mankiw-Romer-Weil equation of the Cobb-Douglas function which takes into account the factor of convergence/divergence and differentiation due to changes in the size of territories, population, volume of economies, and other parameters of the studied states and societies. The applied Theil index makes it possible (since it can be used as a "transition key") to compare the dynamic time series of human capital development in the early industrial and post-industrial, knowledge, as well as the information cycles of economic development. Drawing on the historical experience of four industrial revolutions, our paper finds that, contrary to popular belief, which considers early industrialization to be a largely unfettered process and human capital development to be a by-product, the Industrial Revolutions actually contributed to the formation of human capital by fostering new technologies and opening up opportunities for personal development for a large number of people, as well as creating a large numbers of new jobs and significantly increasing productivity and wages. Our approach makes it possible to calculate the development of human capital for each cycle of economic development according to separate formulas and then compare them in one dynamic series. Our results might be relevant for stakeholders and policy-makers in the countries largely relying upon the export of their natural resources who might want to attempt changing their dependency and to invest in the formation of a knowledge-based economy based on the high-quality human capital.
Keywords: 330; convergence; divergence; dynamic series; economic development; human capital